2023
DOI: 10.3390/microorganisms11061435
|View full text |Cite
|
Sign up to set email alerts
|

Live Biomass of Rigidoporus vinctus: A Sustainable Method for Decoloration and Detoxification of Dyes in Water

Abstract: In this study, white-rot fungus, Rigidoporus vinctus, collected from an unidentified fallen twig from Pathankot, Punjab, India, was used for biosorption of anionic Congo red and cationic Methylene blue dyes from an aqueous medium. The biosorption efficiency of the live biomass of Rigidoporus vinctus was investigated to optimize biosorbent dosage, process time, concentrations of dyes, and pH of solutions. The results indicated that Rigidoporus vinctus is more efficient than other reported bio-adsorbents for Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Figure 2 a and b depict the Langmuir and Freundlich isotherm diagrams, respectively. The Langmuir parameters can be determined by plotting 1/q e against 1/Ce, while the values of Freundlich isotherm parameters were obtained by plotting logq e against logCe 57 . The isotherm analysis results showed that the biosorption process best fits the Freundlich isotherm model, with a correlation coefficient 0.98 and k f = 13.7588, indicating that MWCNT-COOH adsorption on fungal surfaces is heterogeneous and multilayer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 a and b depict the Langmuir and Freundlich isotherm diagrams, respectively. The Langmuir parameters can be determined by plotting 1/q e against 1/Ce, while the values of Freundlich isotherm parameters were obtained by plotting logq e against logCe 57 . The isotherm analysis results showed that the biosorption process best fits the Freundlich isotherm model, with a correlation coefficient 0.98 and k f = 13.7588, indicating that MWCNT-COOH adsorption on fungal surfaces is heterogeneous and multilayer.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar study, the removal of dyes with live biomass of Rigidoporus vinctus showed that the kinetic removal of Congo Red and Methylene Blue dyes by this white-rot-fungus also followed a pseudo-second-order model with a qe = 14.9 and 16.6 mg. g −1 , and k = 0.001 and 0.0006 g/mg/h, respectively 57 . The parameters derived from the isotherm and kinetic models are summarized in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the problem is only expected to worsen [ 1 ]. Most of these pollutants are, but not limited to, colored, containing dyes [ 2 ]. Dyes are generally complex heterocyclic organic structures that are chemically inert.…”
Section: Introductionmentioning
confidence: 99%